Heterogeneous peroral medicinal forms in treatment of digestive disorders - Pantyukhin A.V. (Саратовский научно-медицинский журнал, 2010)
Medicinal form with all its components: auxiliary substances, way of introduction of medicinal substances, favourable properties, appearance and convenience of application influences its therapeutic efficiency. Biological availability of heterogeneous medicinal forms for peroral applications in the form of suspension and emulsion were compared in the research. There were included natural auxiliary substances. Comparative investigations were held on models of experimental gastric ulcer on Okabe and single introduction of hormones. The presented research stated that medical products as components of heterogeneous, correct medicines in the form of suspensions and emulsions positively influence the therapeutic efficiency. Besides, the substances stabilizing heterogeneous systems intensify and supplement pharmacological action of medical product